Pengaruh Kompetensi dan Disiplin Kerja Terhadap Kinerja Pegawai Dinas Sosial Kota Padang - M, Herik Nelson; Haryati, Rice; Delvianti, Delvianti (Ekasakti Matua Jurnal Manajemen, 2023)
The purpose of this study was to determine: 1. The partial effect of work discipline on employee performance. 2. Partial effect on employee performance. 3. The simultaneous influence of work discipline and competence on the performance of Padang City Social Service employees. The population of this study were employees of the Padang City Social Service with a total of 40 people. The sampling technique of this study used the total sampling method. Research data using primary data collected through the distribution of questionnaires to employees. The method of data analysis in this study used multiple linear regression analysis, coefficient of determination and hypothesis testing t and f. The results of the analysis show that 1. Competence partially has a significant positive effect on employee performance. 2. Work discipline partially has a significant positive effect on the performance of Padang City Social Service Employees. 3. Competence and work discipline simultaneously have a positive and significant effect on employee performance. Contribution of Work Discipline Competence to the Performance of Padang Social Service Employees 52.4%, the remaining 47.6% is influenced by other variables outside this research.